Hydrodynamics drives shifts in phytoplankton community composition and carbon-to-chlorophyll a ratio in the northern South China Sea - Chen, Dawei; Shi, Zhen; Li, Ruihuan; Li, Xiangfu; Cheng, Yuanyue; Xu, Jie (Frontiers in Marine Science, 2023)
Phytoplankton play significant role in carbon cycle in oceans. Phytoplankton biomass and community composition are often mediated by hydrodynamics in oceans. It was vital to quantify phytoplankton carbon content and carbon: Chlorophyll a (C: Chl a) ratio and to better understand the link of hydrodynamics and phytoplankton community in marine environments, which were important parameters in marine biogeochemical models. Environmental variables, phytoplankton community composition, abundance, particulate organic carbon and Chl a were determined in summer in the northern South China Sea (SCS), which was influenced by the Pearl River discharge, upwelling and anticyclonic eddy, to examine the links of hydrodynamics, phytoplankton community and C: Chl a ratio. Our results showed that spatial variabilities in phytoplankton community composition and carbon content and C: Chl a ratio were driven by hydrodynamics. Nutrient enrichment favored the growth of diatoms, especially small chainforming diatoms at the Pearl River Estuary stations. From inshore to offshore, the dominant phytoplankton was shifted from small chain diatoms to large diatoms and dinoflagellate, increasing phytoplankton biodiversity from inshore to offshore. The weak upwelling caused an increase in Synechococcus abundance, while anticyclonic eddy had resulted in high abundance of Prochlorococcus and Trichodesmium spp. in the present study. We found that the relationship between phytoplankton carbon content and logarithm of Chl a concentrations fit the exponential curve. The C: Chl a ratios increased from 72.7 g g -1 at Pearl River Estuary stations, to 101 g g -1 at Pearl River discharge dilution stations and to 131 g g -1 at SCS surface stations due to shifts in phytoplankton community composition. Low C: Chl a ratio was attributed to high abundance of diatoms in Pearl River plume-impacted area, while high C: Chl a ratio was related to the dominance of cyanobacteria at SCS surface stations. Our findings provide insights into quantifying phytoplankton carbon content, and understanding the links of hydrodynamics, phytoplankton community composition, carbon content and C: Chl a ratio in oceans.